Produção de celulases por Gelatoporia subvermispora para hidrólise de material celulósico - Reis, Cristiane Bianchi Loureiro dos (2014)
Several microorganisms are able of producing enzymes responsible for the conversion of biomass to ethanol, such as cellulases. However, studies about diversity and biotechnological application of microorganisms from Pampa biome are still scarce. To try to reduce this knowledge lack, the Gelatoporia subvermispora fungus was isolated from the Pampa biome, resulting in the first occurrence of this specie in Latin America. Commercially, cellulases are produced by submerged fermentation. However, filamentous fungi that are considered good producers of cellulases show better results in solid-state fermentation, mainly by the similarity between the solid medium and the natural habitat of these microorganisms. In order to evaluate the biotechnological potential of the fungi G. subvermispora for cellulases production, rice straw, sewage sludge and sugar cane bagasse were used as substrate. The highest values for the total cellulolytic activity by the method of filter paper (FP) were obtained using sugarcane bagasse as substrate, reaching the value of 3.82 FPU.g-1. The sewage sludge was an excellent medium for the production of xylanase and exo-cellulases, reaching peak activity of 227.97 U.g-1 and 134.25 U.g-1, respectively. The endo-cellulase activity was similar in almost whole substrates tested, as showed in the runs 11 for rice straw (40.75 U.g-1) and 14 for sewage sludge (35.32 U.g-1). Subsequently, cellulolytic enzymes from fungal Gelatoporia subvermispora produced by solid-state fermentation using different substrates were applied to hydrolyze non-treated sugarcane bagasse using indirect sonication. The best results were obtained using sewage sludge as substrate for enzyme production. The mean yields obtained with enzymes produced using sewage sludge, sugarcane bagasse and rice straw as substrates were 72.8, 58.7 and 51.2 g.kg-1, respectively. Regarding the use of ultrasound to carry out enzymatic reactions, the oscillation amplitude presented a negative effect on yield, whereas pulse factor showed to be benefic for the reactions.